ITIL IMPLEMENTATION IN SMALL BUSINESS - Piterāns, Artis; Ņemņasevs, Vadims; Pavļukaite, Alīna; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The goal of this work is to develop guidelines of ITIL (Information Technology Infrastructure Library) implementation in small businesses. To achieve goal of this work authors analyzed information about ITIL processes and chose those which necessary for small businesses. Next step was developing guidelines of implementing chosen processes in small businesses. Conclusion was made using knowledge gathered from analyzes.